Evaluasi Pembelajaran Daring PJOK Siswa Kelas II SDN Poris Plawad 3 Kota Tangerang - Huliatunisa, Yayah; Hadi, Romita Umayyah; Rizkiya, Della Fully; Saidah, Mutia; Ningsih, Pinkan Ayu (Lembaga Yasin AlSys, 2022)
Physical education learning focuses on maintaining and improving physical fitness and movement skills in students during the learning process, also helping students to improve critical thinking patterns, maintaining students' emotional stability, and fostering good values contained in sports such as respect and sportsmanship. This study aims to determine the process of evaluating online learning PJOK for grade II students at SDN Poris Palawad 3 Tangerang City, using a qualitative descriptive method. Sources of information in this study were PJOK teachers. Data collection techniques through observation, interviews, and documentation studies. Based on the results of the study, it shows that PJOK online learning uses applications such as whatApp (to collect assignments), zoom or Google meet for the learning process. The teacher presents the material and videos in the application using print media and audiovisual media. Constraints encountered in the online learning process in general are in the form of networks, gadgets/mobile phones, worksheets, and assessments.